2011
DOI: 10.1212/wnl.0b013e3182343314
|View full text |Cite
|
Sign up to set email alerts
|

Predicting MCI outcome with clinically available MRI and CSF biomarkers

Abstract: Incorporating quantitative assessment of learning ability along with vMRI or CSF biomarkers in the clinical workup of MCI can provide critical information on risk of imminent conversion to AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
167
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(178 citation statements)
references
References 45 publications
10
167
1
Order By: Relevance
“…22 This software was evaluated against the manual segmentation, and a good agreement was found between manual and automatic segmentation. 23 However, we cannot compare it with our study because the ICV data were not presented.…”
Section: Discussionmentioning
confidence: 96%
“…22 This software was evaluated against the manual segmentation, and a good agreement was found between manual and automatic segmentation. 23 However, we cannot compare it with our study because the ICV data were not presented.…”
Section: Discussionmentioning
confidence: 96%
“…Shaffer et al biomarker utility have been published from ADNI (11,(18)(19)(20)(21)(22)(23)(24), but relatively few have examined the additive utility of such biomarkers above and beyond routine neuropsychological tests. This is critical because none of the biomarkers are likely to be used clinically before cognition is assessed.…”
Section: Neuroradiology: Alzheimer Disease Conversion Prediction Withmentioning
confidence: 99%
“…This makes their clinical outcomes more ambiguous, because it is possible that such subjects might have converted to AD after their last visit. One study by Heister et al (24), analyzing longitudinal data in subjects with MCI from the ADNI, showed that those who dropped out of the study early but retained the MCI diagnosis at their last visit had greater memory impairment than those who completed the study.…”
Section: Subject Characteristicsmentioning
confidence: 99%
“…The estimation of medial temporal lobe atrophy (MTA) on MRI scans, either visually assessed or evaluated through manual or automatic volumetry, has been found to be a valid marker for the conversion from MCI to dementia [16,17,18]. However, both manual and automatic volumetry methods lack clinical feasibility.…”
Section: Introductionmentioning
confidence: 99%